XEN Glaucoma Implant for the Management of Operated Uncontrolled Glaucoma: Results and Complications during a Long-Term Follow-Up - Katarzyna Lewczuk; Joanna Konopińska; Joanna Jabłońska; Jacek Rudowicz; Patrycja Laszewicz; Zofia Mariak; Marek Rękas (Journal of Ophthalmology)
This study aimed to analyze the surgical and refractive outcomes of XEN glaucoma implant (Allergan, an Abbvie company, Irvine, CA, USA), a minimally invasive surgical device for the treatment of operated uncontrolled glaucoma. Eyes that received XEN Gel Stent placement from December 2014 to October 2019 were retrospectively investigated. Intraocular pressure (IOP) change, best-corrected visual acuity (BCVA), change in glaucoma medications, frequency of slit lamp revision procedures, and frequency of secondary glaucoma surgeries were the primary outcomes. Seventy-two eyes of 72 subjects were included in the study: 32 (44%) men and 40 (56%) women. The follow-up period ranged from 1 to 50 months (median, 26.13 months). The mean IOP before surgery was 24.82 ± 8.03 mmHg and decreased to 17.45 ± 5.84 mmHg at the end of the study (mean difference [MD] = −7.48, 95% confidence interval [CI]: −10.04, −4.93; p<0.001). The mean decrease from baseline was 23%. BCVA before surgery was 0.38 ± 0.30, and that at the end of the follow-up period improved to 0.47 ± 0.37, MD = 0.09, 95% CI: 0.04, 0.13; p<0.001. Additional procedures (fluorouracil injection and bleb needling) were performed in 11/72 patients (15%). Further glaucoma surgery was necessary for 23.9% of the patients. XEN Gel Stent implantation is both safe and reasonably effective for lowering IOP in operated uncontrolled glaucoma patients.